Dental care challenges in Sturge-Weber syndrome: a case report - Fortuna, Tila; de Oliveira, Caroline Argolo Brito; Medrado, Alena Ribeiro Alves Peixoto; de Oliveira, Viviane Maia Barreto; Tunes, Roberta Santos; Marchionni, Antônio Márcio Teixeira (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: Sturge-Weber syndrome (SWS) is a rare condition characterized by facial capillary malformation, involves ocular, neurological, and cutaneous alterations. Associated with unilateral characteristic port-wine stains, gingival growth and purple-red coloration. Aim: his case aims to report dental treatment challenges in patients with SWS and importance of oral health maintenance in these individuals. Case report: a 20-year-old woman with an established diagnosis of SWS, presented bad breath and spontaneous gingival bleeding, with gingival growth and reddish-purple spots spread to labial and alveolar mucosa, tongue, and palate. Conditioning of the patient’s oral environment by supra and subgingival scraping, dental unit extraction was performed. A conservative treatment plan was adopted for management adequacy of oral environment owing to possible complications inherent to the condition. Conclusion: it is important to emphasize the importance of dental surgeon’s performance in relation to a multidisciplinary health team, as well as cooperation of patient, to obtain better results from the proposed therapy